An?lise de desempenho de t?cnicas de comunica??o digital em canais com distribui??o K-? , desvanecimento lento e n?o seletivo em frequ?ncia - Souza, Rausley Adriano Amaral (2002)
The time-varying channels of mobile communication systems can be modeled through statistical distributions such as Rayleigh, Rice and Nakagami-m. This dissertation presents the performance evaluation in terms of mean K-? channel error probability with and without the use of the diversity technique. Graphs, calculated from numerical integration methods, are presented for the average error probability by the SNR ratio, which are compared with the traditional error probability curves. A closed expression is also presented for the calculation of the cumulative distribution function of the K-? distribution when ? assumes integer values. Through the use of statistical methods is presented a methodology for the generation of random variables distributed according to the K-? distribution for any values of K and ?.